Perancangan Sarung Bantal Hias Untuk Sofa Dengan Teknik Makrame - Wati, Erna; Josef, Adji Isworo (Institut Seni Indoensia Surakarta, 2022)
Pillowcase is a place that is used to protect the pillow from dust and dirt. The macrame technique is a knotted knot craft consisting of several ropes or threads to make a work. There are very few macrame pillowcase products on the market, this causes the product to be less popular. Because judging from the manufacturing process looks complicated and takes a long time. So this is the background of the Design of Decorative Pillowcases for Sofas with the Makrame Technique. This design aims to make macrame pillowcase products easy to produce. The creation method used is SP Gustami's theory which consists of 3 stages, namely exploration, design and embodiment. The result of the creation of this work is a sofa cushion cover made using the macrame technique. This sofa cushion cover is intended as a decoration on a sofa or room.Keywords: Pillowcase, Sofa, Macrame